Shakespeare's Hybrid Faith - Mayer, J. author. aut Link
IX, 235 p.
Keywords: This book throws new light on the issue of the dramatist's religious orientation by dismissing sectarian and one-sided theories, tackling the problem from the angle of the variegated Elizabethan context recently uncovered by modern historians and theatre scholars. It is argued that faith was a quest rather than a quiet certainty for the playwright.